Nationwide outcomes of aortic valve replacement for pure aortic regurgitation in Germany 2008–2015. Issue 4 (4th June 2019) - Stachon, Peter; Kaier, Klaus; Heidt, Timo; Bothe, Wolfgang; Zirlik, Andreas; Zehender, Manfred; Bode, Christoph; von zur Mühlen, Constantin
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is routinely used in patients with severe aortic stenosis at increased operative risk. Due to potential technical difficulties, TAVR is not recommended for pure aortic regurgitation (AR). Smaller studies reported its use in AR, but data from big registries are lacking. The present study analyzes the nationwide use of surgical aortic valve replacement (SAVR) and TAVR in patients with AR from 2008 until 2015. Methods: We identified 138, 237 cases of aortic valve replacement in Germany based on ICD and OPS codes. Results: Of 13.2% SAVR‐cases and 1.3% of TAVR cases were performed in AR. AR patients undergoing SAVR were younger with lower logistic EuroSCORE (stenosis: 6.1 ± 5.6; AR: 4.5 ± 4.9). Nevertheless, stroke rates, bleedings, prolonged mechanical ventilation, and in‐hospital mortality were higher (mortality: stenosis 2.6%, AR: 4.7%). In the TAVR group, patients with AR were at higher operative risk (logistic EuroSCORE: transfemoral (TF)‐TAVR: stenosis: 14.3 ± 10.4; AR: 17.3 ± 13.3. Transapical (TA)‐TAVR: stenosis: 16.1 ± 11.4; AR: 15.7 ± 12.2). Stroke rates were lower, but bleedings and prolonged ventilation occurred more frequently after TF‐TAVR in AR compared to stenosis. The mortality varied markedly (TF‐TAVR: 15.2% in 2011; 2.8% in 2015; TA‐TAVR: 17.7% in 2012 and 0% in 2014). Conclusion: TAVR is off‐label used in AR in clinical practice. TAVR seems to be a safe option for AR with regard to in‐hospital outcomes. However, further research evaluating long‐term outcomes is required to establish the feasibility of TAVR in pure AR.